Promotion of arsenic phytoextraction efficiency in the fern Pteris vittata by the inoculation of As-resistant bacteria: a soil bioremediation perspective - Lampis, Silvia; Santi, Chiara; Ciurli, Adriana; Andreolli, Marco; Vallini, Giovanni (Frontiers in Plant Science, 2015)
A greenhouse pot experiment was carried out to evaluate the efficiency of arsenic phytoextraction by the fern Pteris vittata growing in arsenic-contaminated soil, with or without the addition of selected rhizobacteria isolated from the polluted site. The bacterial strains were selected for arsenic resistance, the ability to reduce arsenate to arsenite, and the ability to promote plant growth. P. vittata plants were cultivated for 4 months in a contaminated substrate consisting of arsenopyrite cinders and mature compost. Four different experimental conditions were tested: i) non-inoculated plants; ii) plants inoculated with the siderophore-producing and arsenate-reducing bacteria Pseudomonas sp. P1III2 and Delftia sp. P2III5 (A); iii) plants inoculated with the siderophore and indoleacetic acid-producing bacteria Bacillus sp. MPV12, Variovorax sp. P4III4 and Pseudoxanthomonas sp. P4V6 (B), and iv) plants inoculated with all five bacterial strains (AB). The presence of growth-promoting rhizobacteria increased plant biomass by up to 45% and increased As removal efficiency from 13% without bacteria to 35% in the presence of the mixed inoculum. Molecular analysis confirmed the persistence of the introduced bacterial strains in the soil and resulted in a significant impact on the structure of the bacterial community.